Denys Lombard dan Desakralisasi Proses Sejarah: Denys Lombard and the Desacralization of the Historical Process - Faidi, Ahmad (Nur Science Institute, 2023)
This article is a critical study of “Le carrefour Javanais: essai d'historia globale.” by Dennys Lombard; as one of the most unique Historigraphy works compared to the works of other orientalist historians. The new approaches offered by Denys Lombard, such as the use of reverse periodization and the “cultural geology” approach, have made a valuable contribution to the development of Indonesian Historigraphy in particular. But on the other side, Denys Lombard's writing method which tends to ignore the historical periodization framework, which should be the main characteristic of history, actually makes him ignore the small changes that occurred in the past.